Sex differences between atherogenic index of plasma and α-klotho levels in middle-aged and older adults: NHANES 2007–2016 - Zuo, Cheng; Shen, Zi-Duo; Lu, Yaojun (Frontiers in Endocrinology, 2025)
ObjectiveKlotho is an anti-aging gene, and the α-klotho protein it encodes reportedly has cardiovascular protective effects. The atherogenic index of plasma (AIP) is a novel and comprehensive lipid index that correlates with atherosclerotic burden and is a critical risk factor for cardiovascular diseases. There are no studies examining the relationship between AIP and α-klotho; thus, we aimed to explore this potential association.MethodsData were extracted from the National Health and Nutrition Examination Survey 2007–2016 database, and the relationship between AIP and serum α-klotho levels was analyzed using weighted multivariate linear regression.ResultsAfter adjusting for risk factors, AIP showed a significant negative correlation with the logarithm of serum α-klotho levels in women. The trend analysis and smoothed curve fitting showed a nonlinear dose–response relationship. Threshold effect analysis showed a significant difference in the association between AIP and α-klotho before and after the AIP break point (0.434). Subgroup analyses demonstrated that the negative association of AIP with α-klotho was consistent across subgroups. However, the correlation between AIP and serum α-klotho in men was not significant.DiscussionOur study provides new evidence for sex differences in the association between AIP and serum α-klotho levels.